Analysis of acoustic emission during abrasive waterjet machining of sheet metals - Nazrin, Mokhtar; Gebremariam, M.A.; Mohd Hafizi, Zohari; Azmir, Azhari (IOP Publishing Ltd, 2018)
The present paper reports on the analysis of acoustic emission (AE) produced during abrasive waterjet (AWJ) machining process. This paper focuses on the relationship of AE and surface quality of sheet metals. The changes in acoustic emission signals recorded by the mean of power spectral density (PSD) via covariance method in relation to the surface quality of the cut are discussed. The test was made using two materials for comparison namely aluminium 6061 and stainless steel 304 with five different feed rates. The acoustic emission data were captured by Labview and later processed using MATLAB software. The results show that the AE spectrums correlated with different feed rates and surface qualities. It can be concluded that the AE is capable of monitoring the changes of feed rate and surface quality.